2020
DOI: 10.3390/ijerph17186472
|View full text |Cite
|
Sign up to set email alerts
|

Being in the Moment So You Can Keep Moving Forward: Mindfulness and Rumination Mediate the Relationship between Attachment Orientations and Negative Conflict Styles

Abstract: Attachment insecurity has been associated with negative behaviors during conflict and decreased relationship satisfaction. We theorize that individuals high in attachment anxiety and/or avoidance are less mindful during conflict with their romantic partners, and thus more likely to ruminate. Decreased mindfulness and higher levels of rumination may be important mechanisms in the relationship between attachment insecurity and conflict behavior, as it may be more difficult to engage in constructive problem-solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…In many disorders in which negative rumination is a detrimental symptom (e.g., attachment disorders, binge eating disorders, depression, etc. ), treatments include steps to decrease negative ruminatory tendencies (Dingemans et al, 2017 ; Li et al, 2018a ; Quickert and MacDonald, 2020 ). If positive and negative repetitive thinking are linked, the effectiveness of and compliance with such strategies may be partially dependent upon an individual’s trait repetitive thinking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In many disorders in which negative rumination is a detrimental symptom (e.g., attachment disorders, binge eating disorders, depression, etc. ), treatments include steps to decrease negative ruminatory tendencies (Dingemans et al, 2017 ; Li et al, 2018a ; Quickert and MacDonald, 2020 ). If positive and negative repetitive thinking are linked, the effectiveness of and compliance with such strategies may be partially dependent upon an individual’s trait repetitive thinking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Such research has shown that attachment and rumination were strongly and predictively associated with PTSD. Researchers have further discovered that rumination is a mediator of attachment to physical health and emotional regulation [ 30 , 31 , 32 , 33 ]. However, these associations were estimated in a general population, and whether this association still exists in patients suffering from TIA or stroke was ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, research in this area presents other limitations that should be considered. First, many studies only examine one member of the relationship dyad (e.g., Bogda & Sendil, 2012;Monteoliva et al, 2005;Pistole & Arricale, 2003;Quickert & MacDonald, 2020;Rivera et al, 2011) instead of both (e.g., Creasey, 2002;Molero et al, 2011) although conflict-resolution styles and relationship satisfaction are likely to be influenced not only by individuals' own characteristics and inputs, but also by their partner's. This is generally due to difficulties associated with sample recruitment (Bretz, 2009) and might thus partly explain the lack of clarity and consistency in results, together with the different data collection instruments and the different age range of participants across studies.…”
mentioning
confidence: 99%
“…Furthermore, this evidence is generally obtained from small-size samples of individuals (e.g., Bonache et al, 2019;Du Plessis, 2006;MacDonald et al, 2019;Pistole & Arricale, 2003) or couples (e.g., Bretz, 2009;Creasey, 2002;Guzmán & Contreras, 2012) -in the latter case, samples rarely exceed several hundred-, and participants are often of a wide age range (e.g., da Costa & Mosmann, 2020;Heresi et al, 2014;Paquette et al, 2020;Quickert & MacDonald, 2020;Scheeren et al, 2014), which hinders the extrapolation of results to emerging adults.…”
mentioning
confidence: 99%